How the Nature of Information Affects Binding in Visual Working Memory - Walt, Nicola (My University, 2007)
The question of whether binding information affects the capacity of visual working memory has not been established to date. Different trends in thought have hypothesized different effects for the way information is stored in this memory system. Using a change-detection paradigm this study tested the binding of colour with colour (Experiment 1) and colour with shape (Experiment 2) in visual working memory with the aim of replicating the previously found decrement in binding performance compared to when information is stored separately. In addition, the discriminability of information was manipulated to see if it had an effect on the binding of colour and shape information in visual working memory. In Experiment 1, 12 participants were presented with single coloured or bicoloured patterns and were required to remember the colours of each pattern either separately or bound in relation to each other. A significant negative effect was found when the colours were bound compared to when the same number was stored separately. Also the position of the target colour within the pattern was found to have a differential effect on performance in the binding of colour information and its separate storage. In Experiment 2, two groups of 12 participants were tested using different stimuli, one group with highly discriminable and another with lowly discriminable. Using a mixed design the memory and perception of colour and shape information was compared between and within groups. Like Experiment 1, a poorer performance was found in both groups when information was bound compared to when it was not bound. A differential effect of the discriminability was also found on binding information from within the same dimension (colour and colour) and different dimensions (colour and shape). The effects of feature position in Experiment 1 and discriminability in Experiment 2 have not been found before. Their finding in this study supports the important effect the nature of the information has on the way information is stored in VWM, particularly when this information is bound.
Keywords: psychology